2016
DOI: 10.1080/10410236.2015.1074024
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Reporting on Front Pages of Major Newspapers in Taiwan Violating Reporting Recommendations Between 2001 and 2012

Abstract: Media reporting can lead to the acceptance of incorrect ideas and information by the general public, which in turn can impact behavior. A number of studies have found that suicide reporting in the media can lead to an increase in the suicide rate or copycat suicides. Therefore, the aims of this study are to (a) investigate front-page reporting of suicide in four major newspapers in Taiwan; (b) investigate violation of recommendations for reporting suicide by the four major newspapers in Taiwan; and (c) investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
(44 reference statements)
1
10
0
2
Order By: Relevance
“…In most low-and middle-income countries (LAMICs), the WHO reporting guidelines remain the main reference document guiding media practitioners in reporting suicide. Similar to research findings from many high-income countries (Bolzern et al, 2019;Marzano et al, 2018;McTernan et al, 2018;Stack, 2020;Utterson et al, 2017), recent evidence shows that adherence to the WHO's recommendations and compliance with standard reporting guidelines are still lacking among journalists and media outlets in LAMICs (Arafat et al, 2019;Armstrong et al, 2018;Chandra et al, 2014;Chang & Freedman, 2018;Cheng et al, 2017;Chiang et al, 2016;Chu et al, 2018;Chun et al, 2018;Yang et al, 2013). For example, quality assessment of media reporting of suicide in India, within the lens of the WHO reporting guidelines, shows that reporting of potentially harmful features (e.g.…”
Section: Introductionmentioning
confidence: 61%
“…In most low-and middle-income countries (LAMICs), the WHO reporting guidelines remain the main reference document guiding media practitioners in reporting suicide. Similar to research findings from many high-income countries (Bolzern et al, 2019;Marzano et al, 2018;McTernan et al, 2018;Stack, 2020;Utterson et al, 2017), recent evidence shows that adherence to the WHO's recommendations and compliance with standard reporting guidelines are still lacking among journalists and media outlets in LAMICs (Arafat et al, 2019;Armstrong et al, 2018;Chandra et al, 2014;Chang & Freedman, 2018;Cheng et al, 2017;Chiang et al, 2016;Chu et al, 2018;Chun et al, 2018;Yang et al, 2013). For example, quality assessment of media reporting of suicide in India, within the lens of the WHO reporting guidelines, shows that reporting of potentially harmful features (e.g.…”
Section: Introductionmentioning
confidence: 61%
“…Feng et al [ 17 ] examined the compliance of 2015 newspaper reports about suicide with WHO media guidelines in Guangdong province and found the majority of suicide reports did not comply. Chiang et al [ 18 ] investigated front-page reporting about suicide in four major newspapers in Taiwan between 2001 and 2012 and concluded that reporting of suicide news by the four major Taiwanese newspapers could be improved through regular assessment and observance of the WHO recommendations. These previous studies are limited by focusing on particular regions in China, many of which are higher-income regions outside the mainland People’s Republic of China.…”
Section: Introductionmentioning
confidence: 99%
“…Much lower adherence to the "No photograph" recommendation (about 9%) was also reported by Fu et al [16]. Chiang et al found that suicide was commonly reported on the front page with photographs [17] .…”
Section: Discussionmentioning
confidence: 85%
“…In spite of the wide dissemination and promotion of WHO guidelines for media suicide reporting, most studies report a generally low reported adherence to guidelines and show 10 cultural differences in compliance with various guideline items [16][17][18][19][20][21][22][23][24]. For instance, some countries reported a quite low adherence to providing helpful information and higher adherence with not publishing photographs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation